The Relationship Between Socioecological Factors and Resilience Among Urban Workers During the COVID-19 Pandemic - Puttaporn Onkhamses; Sukanya Tantiprasoplap; Wanna Sanongdej (Jurnal Keperawatan Indonesia, 2025)
The global outbreak occasioned by the coronavirus disease 2019 (COVID-19) has affected people of working age in urban communities, both socially and psychologically, making resilience an important aspect of efforts to cope with such a crisis. Against this backdrop, this study identified and investigated the socioecological factors associated with the resilience of employable urban residents against the COVID-19 pandemic as part of a conceptual framework that encompasses individual, family, and community resilience. This cross-sectional research involved 368 working-age individuals recruited via simple randomization from communities in seven areas in central Bangkok. Data were collected through a questionnaire survey and examined through path analysis run on AMOS. The hypothesized model was tested on the basis of real data (χ2 = 47.717, df = 10, p = .06, RMSEA = .03, RMR .097, GFI .978, CFI .99). The results showed that an individual’s mental resilience factors and those of their family were generally more highly correlated with community resilience than were the resilience of working-age people in urban regions (p < .01). However, the adaptability of working-age individuals in urban areas more strongly depended on family resilience and individual mental health than on community resilience. The results of this study will serve as a foundation for guiding community nurses in the design and implementation of interventions aimed at promoting mental health among working-age individuals and their families. Keywords: COVID-19, mental health, resilience, socioecological, working age   Abstrak Hubungan antara Faktor Sosioekologis dan Ketahanan di antara Pekerja Perkotaan Selama Masa Pandemi COVID-19. Wabah global yang disebabkan oleh penyakit coronavirus 2019 (COVID-19) memberikan dampak pada pekerja di masyarakat perkotaan, baik secara sosial maupun psikologis, sehingga ketahanan menjadi aspek penting dalam upaya mengatasi krisis semacam ini. Studi ini mengidentifikasi dan meneliti faktor-faktor sosioekologis yang terkait dengan ketahanan penduduk perkotaan selama pandemi COVID-19 sebagai bagian dari kerangka konseptual yang mencakup ketahanan individu, keluarga, dan komunitas. Penelitian potong lintang ini melibatkan 368 individu usia produktif yang direkrut melalui randomisasi sederhana dari masyarakat di tujuh wilayah di pusat Bangkok. Data dikumpulkan melalui survei kuesioner dan dianalisis menggunakan path analysis pada AMOS. Model yang dihasilkan diuji berdasarkan data nyata (χ2 = 47,717, df = 10, p = 0,06, RMSEA = 0,03, RMR 0,097, GFI 0,978, CFI 0,99). Hasil menunjukkan bahwa faktor ketahanan mental individu dan keluarga umumnya lebih erat terkait dengan ketahanan komunitas dibandingkan dengan ketahanan individu usia kerja di daerah perkotaan (p < 0,01). Namun, kemampuan beradaptasi individu usia kerja di daerah perkotaan lebih bergantung pada ketahanan keluarga dan kesehatan mental individu daripada ketahanan komunitas. Hasil penelitian ini akan menjadi dasar bagi perawat komunitas dalam merancang dan melaksanakan intervensi yang bertujuan untuk meningkatkan kesehatan mental di kalangan individu usia kerja dan keluarganya. Kata Kunci: COVID-19, kesehatan mental, ketahanan, sosioekologis, usia kerja